The Effect of Project-Based Learning Using E-Learning on Student Learning Outcomes in Vocational Education Courses - Desmira Desmira; Muhammad Sonhaji Akbar; Erik Rahman; Taufik Taufik; Julius Jonas Mbawala (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
The integration of digital technology in higher education has accelerated the need for innovative pedagogical approaches that foster active learning and digital competence. Project-Based Learning (PjBL) supported by e-learning provides authentic, technology-driven experiences that are particularly valuable in vocational education, where students must connect theory with practice. This study examined the effect of PjBL using e-learning on student learning outcomes in vocational education courses at the Department of Information Technology Education, Universitas Negeri Surabaya. A quasi-experimental pretest–posttest control group design was employed with 64 purposively selected undergraduate students from the 2024/2025 academic cohort. Participants were assigned equally to an experimental group (n = 32), which received PjBL integrated with e-learning, and a control group (n = 32), which received conventional lecture-based instruction. Data were collected through pretests and posttests and analyzed using descriptive statistics, independent samples t-test, and effect size calculations. Findings revealed that the experimental group achieved significantly higher posttest scores (M = 84.63, SD = 5.21) compared to the control group (M = 76.88, SD = 6.02). The independent samples t-test confirmed the significance of the difference (t = 5.67, p < 0.001), while Cohen’s d (d = 1.32) indicated a large effect size. These results demonstrate that integrating PjBL with e-learning substantially improves learning outcomes in vocational education. In conclusion, PjBL supported by e-learning offers an effective instructional strategy for enhancing problem-solving, higher-order thinking, and active student engagement. The findings suggest that aligning pedagogy with digital platforms can optimize learning effectiveness and strengthen students’ readiness for professional challenges.